Are We Treating Our Patients Right? A Case of Disseminated Herpes Zoster - Silva, Madalena Sousa; Silva, Isa; Pereira, Luís; Carneiro, António; Rodrigues, Sofia; Fernandes, Natália (Archives of Clinical and Medical Case Reports, 2020)
Varicella-zoster virus infection is a common health problem worldwide, especially affecting the elderly and is responsible for great morbidity. We expose the clinical case of an 89 year old woman who was diagnosed with herpes zoster infection but was only treated with painkillers. The patient was admitted to the hospital, with severe neuropathic pain and a disseminated rash. Though antiviral therapy was started, the patient clinical status was complicated with encephalitis. With this clinical case we wish to emphasize the importance of clinical recognition of herpes zoster infection in order to promptly start antiviral treatment. We also want to enlighten the role of herpes zoster vaccination to reduce the health complications associated to the disease.